Characteristics of patients potentially eligible for pharmacotherapy for weight loss in primary care practice in the United States. (26th May 2016) - Zhang, Shumin; Manne, Sudhakar; Lin, Jennifer; Yang, Jiao
Summary: Objective: To describe the characteristics of real‐world patients potentially eligible for adjunctive pharmacotherapy for weight loss. Methods: Patients from the GE Centricity electronic medical record database were selected if they had body mass index (BMI) ≥30 or ≥27 to <30 kg m −2 with ≥1 obesity‐associated comorbidity (hypertension, dyslipidemia, or type 2 diabetes) from 2002–2011; were aged ≥18 years and had ≥12 months of continuous enrollment before and after the date of first eligible BMI recorded (index date). Descriptive statistics and logistic regression were used for analysis. Results: Of the 1, 835, 541 patients with overweight or obesity included, comorbidities were common (hypertension [55.4%], dyslipidemia [36.1%] and type 2 diabetes [13.4%]). The percentage of patients who received pharmacotherapy for weight loss was 0.7% within 12 months after the index date. Patients who received pharmacotherapy had higher BMI (median, 33.6 vs. 31.3 kg m −2 ), were younger (median, 42 vs. 52 years), primarily women (84.3 vs. 58.2%), commercially insured (70.1 vs. 50.4%) and had more frequent use of antidepressants (30.8 vs. 14.1%) and non‐steroidal anti‐inflammatory drugs (21.7 vs. 12.0%) than those who did not at baseline (all P values < 0.0001). Conclusions: Few eligible patients received pharmacotherapy for weight loss. Patients who received pharmacotherapy tended to be heavier, younger, female, commercially insured, and used more antidepressants and non‐steroidal anti‐inflammatory drugs.